Järnmalm och Kristall : En fallstudie om LKAB:s samhällsansvar vid byggandet av Kiruna nya stadshus - Nilsson Valencia, Josefin (2014)
Something unique is going on in the city of in Kiruna right now. Large areas of the city need to be demolished or moved as a result of LKAB’s mining. There are many companies and people involved and this relocation is globally unique of its extence. How can companies take social responsibility and create value at such significant changes? The city in transformation process is enormous, both in terms of time and number of affected. The City Hall is seen as a symbol of the city and is the first public building to be built in New Kiruna. LKAB is responsible for the construction of the new city hall. This study is a case study of that company and its corporate social responsibility. In this study, empirical primary data have been collected by semi-structured interviews with informed people in charge at LKAB and Kiruna municipality. An understanding of the social transformation process has been acquired through participation in several seminars. The purpose of this study was to describe whether companies can take social responsibility and create shared value with the help of co-branding or repositioning in times of external changes. The study showed that a company and a municipality in a particular situation have much to gain by cooperating. The conclusion is that companies can gain by cooperating and that they can simultaneously take social responsibility that creates shared value for society and their own company. Validerat; 20140818 (global_studentproject_submitter)